Rauisuchia - Nesbitt, S.J.; Brusatte, S.L.; Desojo, J.B.; Liparini, A.; De França, M.A.G.; Weinbaum, J.C.; Gower, D.J. (2013)
'Rauisuchia' comprises Triassic pseudosuchians that ranged greatly in body size, locomotor styles and feeding ecologies. Our concept of what constitutes a rauisuchian is changing as a result of discoveries over the last 15 years. New evidence has shown that rauisuchians are probably not a natural (monophyletic) group, but instead are a number of smaller clades (e.g. Rauisuchidae, Ctenosauriscidae, Shuvosauridae) that may not be each other's closest relatives within Pseudosuchia. Here, we acknowledge that there are still large gaps in the basic understanding in the alphalevel taxonomy and relationships of these groups, but good progress is being made. As a result of renewed interest in rauisuchians, an expanding number of recent studies have focused on the growth, locomotor habits, and biomechanics of these animals, and we review these studies here. We are clearly in the midst of a renaissance in our understanding of rauisuchian evolution and the continuation of detailed descriptions, the development of explicit phylogenetic hypotheses, and explicit palaeobiological studies are essential in advancing our knowledge of these extinct animals. © The Geological Society of London 2013.
Issue: 1 Journal Abbreviation: Geol. Soc. Spec. Publ. Pages: 274 Publication Title: Geol. Soc. Spec. Publ.
Keywords: Triassic; biomechanics; body size; crocodilian; dept.bio; feeding ecology; paleobiology; paleontology; phylogenetics; taxonomy

Is it time for a new paradigm for systemic cancer treatment? Lessons from a century of cancer chemotherapy. - Crawford, Sarah (Frontiers in pharmacology, 2013)
U.S. SEER (Surveillance Epidemiology and End Results) data for age-adjusted mortality rates for all cancers combined for all races show only a modest overall 13% decline over the past 35 years. Moreover, the greatest contributor to cancer mortality is treatment-resistant metastatic disease. The accepted therapeutic paradigm for the past half-century for the treatment of advanced cancers has involved the use of systemic chemotherapy drugs cytotoxic for cycling cells (both normal and malignant) during DNA synthesis and/or mitosis. The failure of this therapeutic modality to achieve high-level, consistent rates of disease-free survival for some of the most common cancers, including tumors of the lung, colon breast, brain, melanoma, and others is the focus of this paper. A retrospective assessment of critical milestones in cancer chemotherapy indicates that most successful therapeutic regimens use cytotoxic cell cycle inhibitors in combined, maximum tolerated, dose-dense acute treatment regimens originally developed to treat acute lymphoblastic leukemia and some lymphomas. Early clinical successes in this area led to their wholesale application to the treatment of solid tumor malignancies that, unfortunately, has not produced consistent, long-term high cure rates for many common cancers. Important differences in therapeutic sensitivity of leukemias/lymphomas versus solid tumors can be explained by key biological differences that define the treatment-resistant solid tumor phenotype. A review of these clinical outcome data in the context of recent developments in our understanding of drug resistance mechanisms characteristic of solid tumors suggests the need for a new paradigm for the treatment of chemotherapy-resistant cancers. In contrast to reductionist approaches, the systemic approach targets both microenvironmental and systemic factors that drive and sustain tumor progression. These systemic factors include dysregulated inflammatory and oxidation pathways shown to be directly implicated in the development and maintenance of the cancer phenotype. The paradigm stresses the importance of a combined preventive/therapeutic approach involving adjuvant chemotherapies that incorporate anti-inflammatory and anti-oxidant therapeutics.
80 citations (Crossref) [2023-10-31] Place: Switzerland Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University New Haven, CT, USA.
Keywords: Adjuvant; Anti-inflammatory; Anti-oxidant; Chemotherapy; Drug resistance; Neoplasm; Tumor microenvironment; Vinca alkaloid; acute lymphoblastic leukemia; adjuvant therapy; advanced cancer; aminopterin; antibiotic agent; antineoplastic activity; antineoplastic agent; antioxidant; article; bladder cancer; bleomycin; brain cancer; breast cancer; cancer cell; cancer chemotherapy; cancer growth; cancer mortality; cancer recurrence; cancer regression; cancer resistance; cancer survival; carboplatin; carmustine; chemosensitivity; childhood leukemia; chlorambucil; chlormethine; choriocarcinoma; cisplatin; colon cancer; cyclophosphamide; dept.bio; disease activity; disease free survival; doxorubicin; drug intermittent therapy; drug megadose; drug tolerability; drug treatment failure; elastin; etoposide; fludarabine; fluorouracil; gemcitabine; head and neck cancer; human; hydroxyurea; infection; inflammation; leukemia; lung cancer; lymphoma; malignant neoplastic disease; maximum tolerated dose; melanoma; mercaptopurine; metastasis; methotrexate; mitoxantrone; multiple cycle treatment; multiple myeloma; nonhodgkin lymphoma; nonhuman; ovary cancer; ovary carcinoma; paclitaxel; pancreas cancer; phenotype; platinum complex; prednisone; procarbazine; solid tumor; systemic therapy; testis cancer; topotecan; tumor microenvironment; unindexed drug; vinblastine; vinblastine sulfate; vincristine

Postcranial skeleton of Postosuchus kirkpatricki (Archosauria: Paracrocodylomorpha), from the upper Triassic of the United States - Weinbaum, Jonathan C (Geological Society, London, Special Publications, 2013)
Postosuchus kirkpatricki is a Late Triassic (Norian) 'rauisuchid' archosaur from North America. The initial description of the Postosuchus type material included elements from two poposaurids. This confusion has prevented adequate description of the material. Recent examination of the type material and other specimens of Postosuchus, and of related taxa, has helped clarify the osteology of Postosuchus. The type specimens represent c. 75% of the skeleton. Together with other referred material, Postosuchus remains one of the most completely known rauisuchids. The paratype skeleton, which is relatively complete, would have been c. 3.5-4 m in length, and the holotype would have been closer to 5-6 m. Analysis of the postcranial skeleton of Postosuchus suggests that it may have been an obligate biped (based in part on limb proportions, which are similar to some theropod dinosaurs, the size of the manus (30% of the size of the pes) and the highly reduced nature of the digits and vertebral measurements). Possible postcranial autapomorphies of Postosuchus include a large, rugose triangular supra-acetabular buttress confluent with the dorsal margin of the iliac blade, and a symmetrical pes with digits two and three being roughly equal in length. © The Geological Society of London 2013.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-386-820-858-734 tex.type: [object Object]
Keywords: Triassic; United States; dept.bio; osteology; peer-reviewed; reptile; skeleton; taxonomy; type specimen